(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2021)
In this paper, we aim to analyze the heat transfer of a torque motor with a limited angle, in special conditions, of space. Three-dimensional models will be used and two current values ​​will be considered. As a working hypothesis, variants will be numerically analyzed in which the boundary conditions (border) will take into account different values ​​of the emissivity of the motor surfaces, varying in the range of 0.2 ÷ 1. Inside the engine subassemblies, the heat transfer will be done by conduction and between the engine and the environment by radiation. With the help of thermal modeling, it will be possible to determine when the winding temperature reaches the maximum allowed value for the torque motor with limited angle, in space conditions.